Comparative physicochemical characteristics and in vitro protein digestibility of alginate/calcium salt restructured pork steak hydrolyzed with bromelain and addition of various hydrocolloids (low acyl gellan, low methoxy pectin and κ-carrageenan). (1st November 2022) - Saengsuk, Nachomkamon; Laohakunjit, Natta; Sanporkha, Promluck; Kaisangsri, Nattapon; Selamassakul, Orrapun; Ratanakhanokchai, Khanok; Uthairatanakij, Apiradee; Waeonukul, Rattiya
Graphic abstract: Highlights: WHC and cooking loss results revealed good retention with added κ-carrageenan. Cohesiveness and springiness were improved with added κ-carrageenan. SEM demonstrated an observable gel network in the structure upon κ-carrageenan addition. LA gellan and κ-carrageenan at 0.5% (w/w) showed high in vitro protein digestibility. Abstract: Physicochemical and in vitro protein digestibility of alginate/calcium (AC) restructured pork steak hydrolyzed with bromelain with addition of LA gellan, LM pectin and κ-carrageenan at various concentrations (0.5, 1.0, 1.5 and 2% w/w) was evaluated for masticatory dysfunction people. The AC samples with κ-carrageenan showed the lowest cooking losses and highest water holding capacity (WHC). Moreover, addition of κ-carrageenan showed the highest Kramer shear force (KSF) and higher hardness, cohesiveness, springiness, chewiness, and gumminess, but the adhesiveness value was lower than those of the other treatments. According to SEM, the gel network of AC samples with κ-carrageenan was more clearly than those with the other treatments. FTIR demonstrated that the addition of polysaccharides to AC sample enhanced the hydrogen bonds in the gel system. For in vitro protein digestibility results, addition of 0.5% (w/w) LA gellan and κ-carrageenan samples showed the highest pepsin (73–74%) and trypsin (79–80%) digestibility.